Imposition of Hands in Confirmation: a medieval problem - Banting, H. M. J. (The journal of ecclesiastical history, 1956)
In the library of Sidney Sussex College, Cambridge, there is a MS. of fourteen leaves which formerly belonged to the priory of Durham. The MS. is of the eleventh century and contains some Pontifical offices, namely the forms of ordination to minor and major orders (with the exception of bishop) and the office of Confirmation. The office of Confirmation begins with an injunction that the bishop shall lay his hand on the head of the candidate. Primitus, impone manum super capud infantis et tangis eum vel eam. Then, after the salutation, follows the prayer for the gift of the Holy Spirit, ‘Almighty and everlasting God, who hast deigned to regenerate thy servant by water and the Holy Spirit and hast given him remission of all his sins, send out upon him from heaven thy sevenfold Holy Spirit, the Paraclete, the spirit of wisdom and understanding, the spirit of counsel and strength, the spirit of knowledge and godliness. Fill him with the spirit of thy fear and graciously sign him with the sign of thy holy cross unto life.’ Then the bishop, having mentioned the candidate's name, makes a cross with chrism on the forehead, saying ‘I sign and confirm thee with the sign of the holy cross in the name of the Father, and of the Son, and of the Holy Spirit’.